Harmonizing metabolic blueprint of flavor using complementary genomic insights - Tiozon, Rhowell Jr. N.; Sreenivasulu, Nese (Cell Press, 2025)
A key component of the eating experience is flavor, which reflects preferred customer desires for higher-quality fruits, vegetables, and cereals. However, the breeders are currently facing difficulty in capturing flavor qualities across the crops, which requires the deployment of multidisciplinary genomics technologies to identify novel alleles and validate the function using genome editing techniques. Luo et al.(2024) recently published in Molecular Plant depicts that flavor traits of waxy corn influenced by preferential selection of brassinosteroid and benzoxazinoid pathway genes (ZmBZR1, ZmUGP1 and the bx genes), impacting significant differences in metabolic pathways of sweet metabolites such as DIMBOA and raffinose. Furthermore, flavor perception in the waxy corn population is unaffected by the desired breeding characteristic of" glutinous" texture.